Neonatal Outcome Associated With Birth Order and Chorionicity in Twin Pregnancy - Pratama, Nur Aprilianita; Gumilar, Khanisyah Erza; Bachnaas, Muhammad Adrianes; Aldika Akbar, Muhammad Ilham (Indonesian Journal of Obstetrics and Gynecology, 2025)
Objectives: The objective of this study is to examine the neonatal outcomes of twin pregnancies based on the difference of chorionicity and order of delivery. Methods: An observational cross-sectional study was done among all women with >24 completed weeks gestation having twin pregnancies in the Department of Obstetrics and Gynaecology of Dr. Soetomo General Hospital and Universitas Airlangga Hospital, Surabaya, Indonesia in 2023. Results: 49 twin from 1638 birth (2.99%) were recruited for the study. The MC groups had a higher prevalence of preterm birth <37 weeks (83.3 vs 53.8%), preterm birth <34 weeks (52.8 vs 15.4%), VLBW (25 vs 7.7%), ELBW (25 vs 15.4%), low Apgar scores at 5th minutes (50 vs 15.4%), admission to NICU (66.7 vs 15.4%), RDS (41.7 vs 7.7%), early neonatal death (33.3 vs 7.7%), and perinatal death (44.4 vs 15.4%) [p<0.05]. In relation to birth order, there were no significant difference in all neonatal outcomes, except the higher prevalence of lower Apgar scores in 1st (75 vs 50%) and 5th minutes (50 vs 19.4) in the second delivered MC twin (p=0.05). Out of the 98 twin babies, there were a total of 32 perinatal deaths (32.65%), consisting of eight stillbirths and twenty-four neonatal deaths. Conclusions: Chorionicity and birth order were influenced by the neonatal outcomes of twin pregnancies. It is important to manage twin pregnancy in specialized or tertiary care center hospital.